Is Data Literacy a Catalyst of Social Justice? A Response from Nine Data Literacy Initiatives in Higher Education - Juliana Elisa Raffaghelli (MDPI AG, 2020)
Is education and more specifically, data literacy initiatives in Higher Education, an appropriate instrument to promote social justice in a context of datafication? Education is (and has been) at the center of the debate over the achievement of social justice as a desirable quality of the human society. However, which type of educational interventions should be promoted to deal with a complex, multi-layered, emergent problem, such is the case of datafication in society? Since the problem is heavily entrenched with a shifting socio-economic model (the so called "surveillance capitalism") and the technological infrastructures connected to it, educational approaches could be diversified and even contradictory in their purpose of heralding the skills to live in a datafied society. This paper explores nine initiatives in Higher Education aimed at developing the literacies to deal with data in society. Their efforts are concentrated in promoting freedom of choice, awareness, and agency. Though their original intention is not promoting social justice, the analysis is carried out on the theoretical basis provided by Martha Nussbaum on social justice. The initiatives span educational activities with open data as open educational resources, to more formal data literacy activities such as educational engagement with students' data and students' personal and educational data. There emerges a still fragmented panorama in responding to the need of promoting social justice in a context of datafication. Given this fragmentation, the article provides a conceptual scheme to address further pedagogical reflection and practice with the aim of supporting social justice against datafication.